Comparative Analysis of DMF Filing Procedure and Regulatory Requirements in India, Brazil, and Canada - Yadav, Saurabh Suresh; Shinde, Sairaj; Sagavkar, Sandhyarani Ramesh; Shete, Amol (Indian Journal of Pharmaceutical Education and Research)
DMF is a confidential document that provides detailed information about the API dosage form in Pharmaceuticals. DMF is also about the drug product. This investigation comprehensively analyses regulatory requirements and Drug Master File filing procedures in India, Brazil, and Canada in three diverse pharmaceutical markets. The analysis explores distinct regulatory agencies governing Pharmaceuticals in each country, including the Central Drug Standard Control Organisation (CDSCO) in India, the Agência Nacional de Vigilância Sanitária (ANVISA) in Brazil, and Health Canada in Canada. Differences along with Commonalities in their DMF filling are explored in detail. Further, the paper outlines the steps involved in DMF filing, including documentation, submission and assessment, closure, and variation in the filling procedure are analyzed. The comparison of DMF filing procedures across regulatory frameworks emphasizes how crucial it is for companies to balance compliance with international standards with specific market demands. This review makes clear the challenges related to DMF filings and the importance of regulatory knowledge for pharmaceutical companies operating in different international markets. The DMF files from Canada, Brazil, and India have several distinctions and parallels. It is essential to comprehend the regulatory organizations, such as Health Canada, ANVISA, and CDSCO. This comparison analysis serves as a valuable resource for industry professionals seeking insight into the intricacies of DMF filing across diverse global pharmaceutical markets.
Keywords: Active Pharmaceutical Ingredient (API); CPID (Certificate Product Information Document); DIFA (Active Pharmaceutical Ingredient dossier or the DMF); MF (Master File); US Food and Drug Administration (USFDA)